ELASTICITY DYNAMICS AND TRADE BALANCE PERFORMANCE AS METRICS FOR FOOD SECURITY – AN ASSESSMENT OF ROMANIA'S SWINE MEAT MARKET - Silviu Ionuţ BEIA; Marius CONSTANTIN; Elena-Mădălina DEACONU; Violeta Elena BEIA; Florea Cosmin NICOLAIE; Dragos SMEDESCU; Cosmina SMEDESCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In addressing the critical interplay between market dynamics and food security within Romania's swine meat market, amidst evolving economic and social challenges, the research aimed to elucidate the roles of elasticity dynamics and trade balance performance in ensuring a high food security level. Utilizing data from 2011 to 2022, the analysis employed key elasticity metrics—price elasticity of demand (PED), income elasticity of demand (IED), factor elasticity of demand (FED), and income elasticity of the swine meat trade balance's deficit (IET)—to dissect the complex interactions configuring demand, supply, and international trade dependencies. The methodology was grounded on quantitative analyses, contrasting year-over-year and base-year elasticities to capture both immediate and longitudinal market responses to socio-economic stimuli. This detailed approach uncovered pertinent findings: despite general price inelasticity in swine meat demand, significant fluctuations in response to income changes and production factors were observed, with 2015 marking a year of heightened sensitivity due to external factors like the African swine fever outbreak. This study underscores the imperative of leveraging elasticity analyses to inform the development of agricultural policies aimed at enhancing domestic production, managing trade deficits, and ultimately reinforcing Romania's food security socio-economic infrastructure against the backdrop of global market volatilities and domestic supply constraints.